Malignant Mixed Mullerian Tumor: An Immunohistochemical Study. (10th July 2012) - Bing, Zhanyong; Pasha, Theresa; Wang, Li-Ping; Zhang, Paul J.
Abstract : Malignant mixed Mullerian tumor (MMMT) is an uncommon aggressive neoplasm composed of both malignant epithelial and mesenchymal components. In this study, immunohistochemical stains of germ cell markers, including SALL4, OCT3/4, glypican-3, and alpha-fetal protein (AFP), and CDX2 were performed in a series of MMMTs. SALL4 nuclear immunoreactivity was detected in 6 out of 19 cases (33%). The staining extent ranged from focal to extensive. The staining intensity was usually intermediate to strong (the score ranged from 1.5 to 3, and average score was 2.3 ± 0.5 in the positive cases). In addition, glypican-3 cytoplasmic reactivity was detected in 14 out of 16 cases (88%) with a mean score of 1.8 ± 0.7 (score ranging from 1 to 3). In contrast, OCT3/4 was only positive in 1 out of 19 cases and AFP in 2 out of 18 cases (11%). In summary, SALL4 and glypican-3 were frequently expressed in a subset of MMMTs. Their roles in the pathogenesis and biology of MMMT are yet to be determined. MMMT should be included in the differential diagnosis when a tumor is positive for SALL4 and/or glypican-3.